2021
DOI: 10.3389/fgene.2021.666833
|View full text |Cite
|
Sign up to set email alerts
|

MiR-3614-5p Is a Potential Novel Biomarker for Colorectal Cancer

Abstract: MiR-3614-5p has been found in a variety of cancers including colorectal cancer. However, the association of miR-3614-5p with colorectal cancer is still unclear. Based on the Cancer Genome Atlas (TCGA) database, the relationship between miR-3614-5p and colorectal cancer can be proved. Wilcoxon rank-sum test was used to compare the miR-3614-5p expression in colorectal cancer tissues and under normal conditions, respectively. The logistic regression method was further employed to analyze the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Although no other studies have reported the role of miR-3614-3p in the pathology of BC, the -5p of this miR gene has been reported to be associated with colon cancer. From this reporting, miR-3614-5p was identified to suppress the proliferation of colon cancer cells through inhibition of the P53 pathway and p38MAPK pathway ( 10 ). However, other functional roles of miR-3614 in cancer development and pathology remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Although no other studies have reported the role of miR-3614-3p in the pathology of BC, the -5p of this miR gene has been reported to be associated with colon cancer. From this reporting, miR-3614-5p was identified to suppress the proliferation of colon cancer cells through inhibition of the P53 pathway and p38MAPK pathway ( 10 ). However, other functional roles of miR-3614 in cancer development and pathology remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In the published data, miR‐3614‐5p is related to various types of cancer. For example, bioinformatics analysis was used to screen for new biomarkers for CRC, and miR‐3614‐5p was identified as a biomarker that predicts the survival and prognosis of patients with CRC 34 . miR‐3614‐5p is significantly downregulated in nonsmall cell lung cancer 35 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, bioinformatics analysis was used to screen for new biomarkers for CRC, and miR-3614-5p was identified as a biomarker that predicts the survival and prognosis of patients with CRC. 34 miR-3614-5p is significantly downregulated in nonsmall cell lung cancer. 35 In hepatocellular carcinoma, miR-3614-5p inhibits malignant progression by regulating YY1.…”
Section: Rfc5 Knockdown Inhibits Crc Progression and May Affect The V...mentioning
confidence: 96%
“…7,8 In addition, an increasing number of studies have suggested the role of aberrant miRs as biomarkers in various cancers, including CC. [9][10][11][12] Notably, an earlier study on miRNA expression profiles in HPV infected CC patients has found that the expression levels of miR-3653 in HPV infected CC tissues were significantly higher than that in normal cervical tissues without HPV infection. 13 However, the relationship between aberrant expression of miR-3653 and HPV infection is unclear.…”
Section: Introductionmentioning
confidence: 99%